(3OQhS aj GdadSaI (B/s - (3cQe, jhSas 1886-1959; (3eOchQ, EHQGgje,s 1902-1995 ((3GdOeGe, GdeedcI GdYQHjI GdSYhOjI(B:s (3GdQjGV(B,(3GdeedcI JGYQHjI GdSYhOjI(B:s (3LOI, GdeedcI GdYQHjI GdSYhOjI (B:s (3ecJHI GdeJfHj,s, 2019)
(3gPG GdcJGH jYJHQ GdGNJjGQ GdeKGdj dWGdH GdadSaI djchf eYGQag GdadSajI GdCSGSjI GdeJVefI dCge GdeUWdMGJ hGdePGgH GdadSajI hBQGA CYdGe GdadSaI HGdEVGaI Edi JZWjJg deSGMI hGSYI LOG efP HhGcjQ GdacQ GdadSaj aj GdTQb hGdZQH hUhdG ddadSaI GdjhfGfjI aj eQGMdgG GdeNJdaI Ke GdadSaI GdhSjWI GdeSjMjI hGdESdGejI HeG aj Pdc Yde GdcdGe hMJi adSaI YUQ GdfgVI hJOTjf adSaI GdJfhjQ hGdMOGKI eY OjcGQJ hGSHjfhRG hcGfW hjJejR GdcJGH HSghdJg hhVhMg eY LRGdI CSdhHg GdCOHj adG gh adSaj afj eYbO hdG gh UMGaj eHJPd hbO bGe Ydi JCdjag YGdeGf ef cHGQ CYdGe GdadSaI GdYQHjI hgeG jhSa cQe hEHQGgje eOchQ(B.s
(3hQO Ydi GdZdGa GdNdaj (B: By Usama Taha.s
(3HHdjhLQGajI (B: (3UaMI (B413-419.s
Keywords: (3GdadSaIs -- (3JGQjNs